2017
DOI: 10.1073/pnas.1709048114
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia cenocepacia integrates cis -2-dodecenoic acid and cyclic dimeric guanosine monophosphate signals to control virulence

Abstract: Quorum sensing (QS) signals are used by bacteria to regulate biological functions in response to cell population densities. Cyclic diguanosine monophosphate (c-di-GMP) regulates cell functions in response to diverse environmental chemical and physical signals that bacteria perceive. In , the QS signal receptor RpfR degrades intracellular c-di-GMP when it senses the QS signal-2-dodecenoic acid, also called diffusible signal factor (BDSF), as a proxy for high cell density. However, it was unclear how this result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 36 publications
3
60
0
Order By: Relevance
“…Here we attempted to link the expression changes of QS related genes with the changes in virulence factors. Cyclic diguanylate monophosphate (c-di-GMP) is an important global signaling molecule that can regulate diverse bacterial physiological processes through its downstream receptors such as biofilm formation [39] and virulence [40,41]. However, c-di-GMP and c-di-AMP signaling have been rarely studied in oral biofilms [42].…”
Section: C2 Vs C3mentioning
confidence: 99%
“…Here we attempted to link the expression changes of QS related genes with the changes in virulence factors. Cyclic diguanylate monophosphate (c-di-GMP) is an important global signaling molecule that can regulate diverse bacterial physiological processes through its downstream receptors such as biofilm formation [39] and virulence [40,41]. However, c-di-GMP and c-di-AMP signaling have been rarely studied in oral biofilms [42].…”
Section: C2 Vs C3mentioning
confidence: 99%
“…requires targeting the upstream region of the QS signals. Among these factors, RpfFR homologues function as the master QS regulators within Burkholderia QS pathways (11,32,40). Moreover, these homologs display high sequence similarity and structural similarity (28), making them attractive targets for Burkholderia QS inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…14-Me-C 16:⌬2 decreases AHL signal production. Recent studies showed that the BDSF system controls AHL signal production by regulating the expression of the AHL synthase CepI at the transcriptional level (9,11). We next sought to measure AHL signal production in the wild-type H111 strain in the presence or absence of 14-Me-C 16:Δ2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The BDSF system relies on the biosynthesis of BDSF signals by the bifunctional crotonase RpfF Bc and the BDSF receptor protein RpfR, which contains PAS‐GGDEF‐EAL domains (Boon et al ., ; Bi et al ., ; Deng et al ., ). BDSF signals bind to RpfR and stimulate cyclic dimeric guanosine monophosphate (c‐di‐GMP) phosphodiesterase activity, thus decreasing intracellular c‐di‐GMP levels and consequently modulating the transcription of target genes by activating the RpfR‐GtrR complex (Deng et al ., ; Udine et al ., ; Yang et al ., ). The BDSF system controls many biological functions in conjunction with the CepIR system (Schmid et al ., ; Deng et al ., ).…”
Section: Introductionmentioning
confidence: 97%